Consumer search, productivity heterogeneity, prices, markups, and pass-through: Theory and estimation - Alex Chernoff; Allen Head; Beverly J. Lapham (Queen's University, Department of Economics, 2024)
We develop and estimate a search model in which identical consumers trade with price-setting firms that differ in productivity. In the model, equilibrium distributions of both prices and markups are non-degenerate and continuous with a firm's price decreasing in its productivity. Variation in the markup across firms is more complicated and depends on both the search process and the distribution of productivity. The model parameters governing each of these are estimated using firm-level data on retail industries in Canada. We use the estimated model to characterize the qualitative and quantitative differences in prices and markups across firms. These differences stem from firm-level variation in demand elasticities driven by productivity heterogeneity and imperfect information about prices. Additionally, we derive analytical expressions to determine how individual firm prices and markups respond to cost and demand changes. This allows us to analyze empirically heterogeneity in firm-level price and markup pass-through. Our findings reveal substantial heterogeneity in pass-through across firms, highlighting the distributional impact of shocks across consumers purchasing in different regions of the price distribution. Finally, our analysis underscores the importance of accounting for individual firm price and markup adjustments to fully understand pass-through to average prices.
Keywords: L11; D43; E31; 330; Markups; Productivity; Firm Heterogeneity; Search; Pass-through